Representasi Problematika Masyarakat Indramayu dalam Novel Telembuk Karya Kedung Darma Romansha - Rizma Febrianti; I Made Sujaya; I Kadek Adhi Dwipayana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research is a qualitative descriptive research that describes the problem of Indramayu society in the novel Telembuk by Kedung Darma Romansha. The theory used in this research is the theory of literary sociology that focuses on literary work. Data collection techniques use library techniques with careful reading, recording, and describing. Research data presentation techniques use informal techniques using descriptions as explanations. The instrument in this research is the researcher himself. The source of the research data used the novel Telembuk by Kedung Darma Romansha published by Book of Mojok. The results of the research are as follows: the problems of Indramayu society in the novel Telembuk there are six, i.e. (1) economic problems, (2) juvenile misconduct, (3) family disorganization, (4) violation of norms, (5) crime, and (6) women's problems.